1995
DOI: 10.1007/bf00037677
|View full text |Cite
|
Sign up to set email alerts
|

Cell and tissue cultures of Catharanthus roseus: A literature survey

Abstract: The literature concerning the regulation and the biosynthesis of secondary metabolites in cell and tissue cultures of Catharanthus roseus is reviewed. The aim of this review is to summarise the progress achieved since the previous review of this subject from 1988 to December 1993. Several factors influencing the production of indole alkaloids are discussed. Special attention is given to large-scale cultivation methods. Some economic considerations on the production of ajmalicine are also discussed. ranth~ ro~e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(101 citation statements)
references
References 151 publications
(109 reference statements)
0
100
0
Order By: Relevance
“…Vitamins and organic components had slight effect on the alkaloids production. Only in case of glucose positive effect on ajmalicine production in hairy-root culture was noted by Moreno et al (1995). On the other hand, Zhao et al (2001) showed that the addition of succinic acid, tryptamine and tryptophan to the culture medium caused significant growth of ajmalicine and catharanthine levels.…”
Section: Resultsmentioning
confidence: 98%
“…Vitamins and organic components had slight effect on the alkaloids production. Only in case of glucose positive effect on ajmalicine production in hairy-root culture was noted by Moreno et al (1995). On the other hand, Zhao et al (2001) showed that the addition of succinic acid, tryptamine and tryptophan to the culture medium caused significant growth of ajmalicine and catharanthine levels.…”
Section: Resultsmentioning
confidence: 98%
“…VBL and VCR are produced as a result of a condensation of the Iboga alkaloid catharanthine and the aspidosperma alkaloid vindoline. While catharanthine-accumulating cell suspension cultures have been successfully produced (Moreno et al, 1995), cultures that make vindoline have never been reported. The complex regulation of vindoline biosynthesis, including the requirement for light and the involvement of several cell types in its production (St Pierre et al, 1999), could not be reproduced in cell culture systems.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenoid indole alkaloid biosynthesis in Catharanthus roseus is one of the best studied elicitorinduced secondary metabolic pathways. In suspension cells, the perception of yeast extract (YE) leads to the activation of terpenoid indole alkaloid biosynthesis (5). Two genes involved in terpenoid indole alkaloid biosynthesis, encoding strictosidine synthase (STR) and tryptophan decarboxylase (TDC), are coordinately regulated and their mRNAs accumulate transiently after YE treatment (6,7).…”
mentioning
confidence: 99%